Otomatisasi Sistem Fertigasi Tetes untuk Tanaman Berbasis Mikrokontroler - Rosma, Iswadi Hasyim; Sukma, Dian Yayan; Solihin, Ikhram Minata (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2021)
The process of manual fertilization and irrigation of plants has disadvantages such as it requires human labor and is inefficient in the use of fertilizers and water sources. Therefore, the purpose of this research is to design and develop an automatic fertigation system. The method used in this research is a drip fertigation technique where the fertigation liquid that has been stirred is placed in a tank with 100 cm height from ground. With the gravitational force, the fertigation liquid is distributed through pipes, hoses and emitters around the plant. While the control system and automation of fertigation distribution to plants is carried out based on a microcontroller that need the condition of soil moisture values around the plant. If the watering time and humidity values are met, the electronic valve will open so that the fertigation liquid flows from the tank to the plants. Furthermore, in this study the tests were carried out to determine the uniformity coefficient and debit of drip fertigation. From the results, it shows that the emitter’s debit influenced by the liquid level in the tank. The uniformity coefficient obtained in the two tests is greater than 90%. From the two tests carried out from the moisture sensor 1 and 2, it shows the mean percentage error for both sensor is less than 1.7%, while the percentage error of soil moisture sensor 1 is 1.6% and the percentage error of soil moisture sensor 2 is 1%, respectively. Meanwhile, from the ultrasonic sensor testing it was obtained 0% of error. It also shows from the testing conducted that the fertigation system works very well and successfully.